On the distribution of decapod crustaceans from the Magellan Biogeographic Province and the Antarctic region - Enrique E. Boschi; María A. Gavio (Scientia Marina, 2005)
The distribution of decapod crustaceans in the southernmost areas of South America and the Antarctic is assessed considering the Magellan Biogeographic Province instead of the antiboreal region. Possible associations between decapod crustaceans from the Magellan Biogeographic Province and those from the Antarctic region are analysed. Species records were assigned to seven geographic regions that were clustered using multivariate analyses based on species presence/absence and Bray-Curtis similarity. The results showed two well-established clusters, one of which included the Pacific and Atlantic areas of the Magellan Province, the southern tip of South America and the Kerguelen Arc islands, with the highest similarity between the southern tip and the Atlantic area. Another cluster was well separated and included the Antarctic and South Georgia with the highest similarity index. Earlier studies and results obtained here suggest that the faunas of southern Chile and southern Argentina are biogeographically related. There is a low level of association among decapod species from the circum-Antarctic region and the Magellan Province.